Implementation of Three Centers of Education Through Synergy Between Teachers and Parents in Strengthening the Practice of Islamic Religious Education Values - Ibnu Abas; Nasaruddin Nasaruddin; Umar Umar; Ade S Anhar (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
Although students have an adequate cognitive understanding of the values ​​of Islamic Religious Education (PAI), various phenomena in the school, family, and community environments indicate that this knowledge has not been fully internalized in daily empirical practice, so that an educational approach is needed that can bridge the gap between aspects of knowledge, attitudes, and religious behavior through collaboration between educational centers. This study aims to analyze the implementation of synergy between teachers and parents within the framework of the Tri-Centre of Education at SDIT Annida as a strategy to strengthen the practice of Islamic Religious Education values ​​in students through the integration of the roles of schools, families, and the social environment. The study uses a qualitative approach with a case study design, involving the principal, Islamic Religious Education teachers, homeroom teachers, parents, and students as research subjects. At the same time, data is collected through observation, in-depth interviews, documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña with validity tests through triangulation of sources, techniques, and time. The results of the study indicate that synergy between teachers and parents is built through intensive communication, alignment of religious habituation programs, guidance on worship and morals at home, continuous monitoring of character development, and joint evaluations that result in consistent practice of Islamic Religious Education values ​​in students' lives at school and in the family environment. These findings confirm that the implementation of the Tri-Sentra Pendidikan is an effective collaborative model in building sustainable religious character education and can be used as a conceptual and practical reference for developing policies to strengthen character education in various Islamic elementary education units.